Analisis Peran Kepala Madrasah Sebagai Supervisor Dan Penilaian Prestasi Kerja Guru Di Madrasah Aliyah Negeri 1 Martapura Kabupaten Banjar Provinsi Kalimantan Selatan - Suraijiah (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This paper is the result of a field study conducted by the MPI Study Program Research Team on the role of the Madrasah Head as Supervisor and Teacher Job Assessment at Madrasah Aliyah 1 Martapura, Banjar Regency, South Kalimantan. The focuses studied include; The role of the Head of Madrasah as a supervisor, the role of the Head of Madrasah in assessing teacher performance and Factors influencing the Head of Madrasah in the Assessment of Teacher Work Performance. The subject of the study was the head of the madrasa as the Top Leader at MAN 1 Martapura. The analysis process is carried out by examining all data generated from interviews, observations and documentation results related to the role of the head of MAN Martapura 1 as Supervisor and assessment of teacher work performance, as well as the factors that influence it. 1 Martapura is quite well implemented with the role of the madrasa head as coordinator, consultant, group leader and evaluator also influenced by several factors, namely educational background, teaching experience, funds and infrastructure. Another finding from the results of this study shows that the success of a madrasa is actually the result of cooperation and shared responsibility of all components in the school, so it is necessary to build synergy in the management of a madrasa. Teacher achievement assessment is very important as a benchmark for teacher achievement.